1993
DOI: 10.1111/j.1432-1033.1993.tb17695.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear matrix of the lower eukaryote Physarum polycephalum and the mammalian epithelial LLC‐PK1 cell line

Abstract: Agarose-encapsulated nuclear matrix preparations of the lower eukaryote Physarum polycephalum and the mammalian renal epithelial LLC-PKJ cell line were analyzed after various experimental protocols with respect to the protein composition. The effect of the mode of deproteinization (2 M NaC1,0.25 M ammonium sulfate or 25 mh4 lithium diiodosalicylate), presence of 2-mercaptoethanol, Ca", Cu2+, chelating agents, the sequence of protein extraction and nuclease digestion, the use of RNase, the temperature at which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…The many nuclei within a single plasmodium progress through the cell cycle synchronously, and at the end of the G 2 phase undergo closed mitosis. Because of these characteristics, several investigators have examined the P. polycephalum nuclear matrix (1)(2)(3)(4) and reported that, as with mammalian nuclear matrix, the P. polycephalum matrix contained a number of proteins ranging from approximately 40 kDa to more than 100 kDa but that it differed from mammalian nuclear matrix by having two dominant proteins with reported molecular masses of 23-28 and 35-38 kDa as determined by SDS-PAGE. 1 The same proteins have also been found associated with purified rDNA chromatin (5).…”
mentioning
confidence: 99%
“…The many nuclei within a single plasmodium progress through the cell cycle synchronously, and at the end of the G 2 phase undergo closed mitosis. Because of these characteristics, several investigators have examined the P. polycephalum nuclear matrix (1)(2)(3)(4) and reported that, as with mammalian nuclear matrix, the P. polycephalum matrix contained a number of proteins ranging from approximately 40 kDa to more than 100 kDa but that it differed from mammalian nuclear matrix by having two dominant proteins with reported molecular masses of 23-28 and 35-38 kDa as determined by SDS-PAGE. 1 The same proteins have also been found associated with purified rDNA chromatin (5).…”
mentioning
confidence: 99%
“…Grabber et al [14] and Eberharter et al [15] demonstrated that intermediate fibre protein was the component of the nuclear matrix. Some previous experiments indicated that a 37 kD polypeptide which is equivalent to tropomyosin in molecular weight existed in the nucler matrix and chromosome scaffold [15,[17][18][19][20], and this polypeptide might represent tropomyosin [19]. Our experiments of protein analyses showed that a 37 kD polypeptide was present in the nuclear matrix and chromosome scaffold of P. polycephalum, which is consistent wf previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The main component of nuclear matrix and chromosome scaffold is nonhistone proteins [1][2][3][4], [10]. Although many biochemical and immunocytochemical analyses have been conducted concerning protein composition of the nuclear matrix and chromosome scaffold, only a few proteins (such as topoisomerase II) have been identified [11][12][13][14][15][16]. Some previous biochemical analyses indicated that a polypeptide of about 37 kD, which is equivalent to tropomyosin in molecular weight, existed in the nuclear matrix and chromosome scaffold [15], [17][18][19][20] and this polypeptide might represent tropomyosin [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these reports the investigators have taken into consideration the effect on nuclear matrix structure of RNAse A (Kaufmann et al 1981;Belgrader et al 1991), of reducing or oxidative chemicals (Dijkwel and Wenink 1984;Kaufmann and Shaper 1984;Stuurman et al 1992a), and of different extracting agents (Belgrader et al 1991;Eberharter et al 1993). Surprisingly, however, the effect of different concentrations of Mg ++ ions during nuclear preparation to obtain the matrix has never been investigated.…”
Section: Discussionmentioning
confidence: 99%